Becoming a [COVID] student?: assessing the impact of COVID-19 on first-year students' experiences of higher education in the Eastern Cape, South Africa - Nebbe, Kelsey Ann (Rhodes University, Faculty of Humanities, Department of Anthropology)
In 2020, the COVID-19 pandemic disrupted South African higher education which forced the shift to emergency distance learning to save the academic years of 2020-2022. The repercussions of this are still emerging, but current literature focuses on understanding the impact of first-year students is focused on the impact of academics caused by the emergency shift to online, the "double transition" as Nyar (2021) termed the adjustment to university and then again to the online emergency academics. There is also a niche for holistic research to be done regarding the student experience - pandemic times and elsewise. My thesis focuses on the journey of studenthood of three cohorts at a residential university in the Eastern Cape, South Africa, through the COVID-19 pandemic of 2020-2022. This research utilises ethnographic iterative mixed methods (questionnaire, interviews, focus groups and participant observation) and the theoretical lens of Rites of Passage to understand my research participant's experiences. My findings are that due to the circumstances of an incomplete student experience of just online academics provided an continuous liminal period for first-year students of 2020-2021, with little to no opportunity for them to develop a connection to the university community. The opportunity for them to holistically become students arises at the end of the pandemic in 2022, with the restrictions lifting and the return to on-campus and in-person academic activities allowing them to have a first-year experienced that COVID-19 prohibited.
Keywords: Rite of passage; COVID-19 Pandemic, 2020-2023 Influence; College freshmen -- South Africa -- Eastern Cape; Liminality; Communitas